Structural and functional properties of hydrolyzed/glycosylated ovalbumin under spray drying and microwave freeze drying - Lili Liu; Xiaoning Dai; Huaibin Kang; Yunfeng Xu; Weiming Hao (Food Science and Human Wellness)
Ovalbumin (OVA), the main protein in egg white, affects most of the functional properties of egg white protein in food processing. The aim of this study was to investigate the effects of spray drying (SD) and microwave freeze drying (MFD) on the preparation of hydrolyzed/glycosylated ovalbumin (HGOVA) and provide useful information on the applications of egg protein powders in the food industry. Results demonstrated that the structure of HGOVA was considerably changed, and its functional properties were improved compared with those of native OVA. SD and MFD processing did not lead to dissociation of HGOVA subunits. SD-HGOVA exhibited higher protein solubility, emulsifying activity, foaming capacities, and gel hardness than MFD-HGOVA. However, MFD-HGOVA was better than the SD-HGOVA in terms of color, emulsion stability, foam stability, water/oil absorption capacity, and thermal stability. Selection of an appropriate drying method could enhance the potential applications of HGOVA in the food industry. Keywords: Ovalbumin, Glycosylation, Spray drying, Microwave freeze drying